Post-Colonial Trends in Income Inequality in Mexico and Brazil : Comparative Analysis - Slavin, Natali; Sejkora, Jiří, 1985-; De Castro, Tereza; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2025)
This master’s thesis examines the impact of colonial institutions established in Mexico and Brazil on the evolution of post-colonial income inequality, offering a side-by-side comparison of this development in both countries. Building on the work of Acemoglu, Robinson, and others, it investigates the possible long-lasting effects of extractive colonial institutions on structural underdevelopment and inequality patterns in the two selected countries, which both currently exhibit signs of high structural income inequality. To fulfill this aim, historical-logical method was applied to key colonial systems and institutions – such as the encomienda and hacienda in Mexico, and sesmaria, engenho, and slavery in Brazil – discovering that, in both cases, these have given rise to the latifundium-minifundium land tenure structure having a further impact on socioeconomic disparities. The historical-comparative method was then applied, revealing that, despite markedly different pre-colonial and early colonial conditions leading to relatively divergent patterns of labor inequality, the two countries experienced post-colonial institutional convergence in terms of land inequality.
Vedoucí práce: Jiří Sejkora
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor dipl. práce]; diplomové práce; master's theses